Constructions of “otherness” and the role of education: The case of Ethiopia - MengStie, SiSay (Journal of Education Culture and Society, 2020)
This article attempts to discuss the concept of constructing “otherness”, the techniques to be used and the role of educational systems. Ethiopia as amultilingual and multicultural country is the basis of discussion for this concept. hence, the writer pays due attention to answer the question: how far the Ethiopian educational policy is designed to reflect diversified group interests fairly, if not equally? Therefore, major theoretical assumptions on construction of “otherness” and some practical experiences of the Ethiopian educational systems are thoroughly examined in this paper.